Designing Good Labour Market Institutions: How to Reconcile Flexibility, Productivity and Security? - Werner Eichhorst; Arne Kalleberg; André Portela de Souza; Jelle Visser (Institute of Labor Economics (IZA), 2019)
The world of work is in constant change. Demographic shifts, technological innovation, institutional reforms and global economic integration affect the way people work. Technological innovations have a major impact on occupations and industries, changing the ways economies in different world regions, in both developed and developing countries, work along with new division of labour that are facilitated by global economic integration. This paper is based on the joint work within the International Panel on Social Progress. It highlights three main areas of attention: a) skill formation, d) the challenges to collective bargaining, and e) social protection and labour market policies. Based on an assessment of the existing evidence, the paper suggests some policy principles and concrete policy options that might further those objectives, not ignoring some tensions that might exist between flexibility and security in the different labour markets. The ultimate direction of reforms in line with an idea of social progress lies in institutional arrangements that facilitate the reconciliation of flexibility and productivity with access to decent jobs and social protection. We argue that distinct policy options are available that can be implemented more globally in order to achieve these goals simultaneously.
Keywords: J21; J24; J52; J81; 330; future of work; industrial relations; skill formation; social protection; non-standard work